Genomic and proteomic evidences unravel the UV-resistome of the poly-extremophile Acinetobacter sp. Ver3 - Kurth, Daniel; Belfiore, Carolina; Gorriti, Marta F.; Cortez, Néstor; Farias, María E.; Albarracín, Virginia H. (Frontiers in Microbiology, 2015)
Ultraviolet radiation can damage biomolecules, with detrimental or even lethal effects for life. Even though lower wavelengths are filtered by the ozone layer, a significant amount of harmful UV-B and UV-A radiation reach Earth’s surface, particularly in high altitude environments. High-Altitude Andean Lakes (HAAL) are a group of disperse shallow lakes and salterns, located at the Dry Central Andes region in South America at altitudes above 3,000 m. As it is considered one of the highest UV-exposed environments, HAAL microbes constitute model systems to study UV-resistance mechanisms in environmental bacteria at various complexity levels. Herein, we present the genome sequence of Acinetobacter sp. Ver3, a gammaproteobacterium isolated from Lake Verde (4,400 m), together with further experimental evidence supporting the phenomenological observations regarding this bacterium ability to cope with increased UV-induced DNA damage. Comparison with the genomes of other Acinetobacter strains highlighted a number of unique genes, such as a novel cryptochrome. Proteomic profiling of UV-exposed cells identified up-regulated proteins such as a specific cytoplasmic catalase, a putative regulator, and proteins associated to amino acid and protein synthesis. Down-regulated proteins were related to several energy-generating pathways such as glycolysis, beta-oxidation of fatty acids and electronic respiratory chain. To the best of our knowledge, this is the first report on a genome from a polyextremophilic Acinetobacter strain. From the genomic and proteomic data, an “UV-resistome” was defined, encompassing the genes that would support the outstanding UV-resistance of this strain.